Desarrollo de una planta piloto de materiales magnéticos - Pagnola, Marcelo Rubén (2018)
This paper presents the development achieved in the FONARSEC project execution, incorporated into the database of the Technological and Social Development Projects with which the assembly of a Magnetic Materials Pilot Plant of semi-industrial nature has been achieved for production of cores used in electrical and/or electronic industry. Unique assembly, due to its peculiarities, in Latin America and within the Mercosur scope, related to the energy sector. This plant produces amorphous and nanocrystalline magnetic materials that increase the effciency of some industrial equipment by up to 80%. This development has been achieved with the participation of two PyMEs that have contributed to generating this R&D platform in a Public and Private Associative Consortium that provides assistance to those interested in this technology.